Retrospective Study on Suicidal Cases at Sir Salimullah Medical College Morgue House in the Year 2008 - Das, Tejendra Chandra; Rahim, Mostaque; Hoq, Md Nazmul; Ahmed, Mosahef Uddin; Yasmin, Sharmin; Sarker, Tamim Rahman (Bangladesh Medical Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Suicide is one of the commonest causes of unnatural death in the world. The number of suicide is increasing over the period of time. Our research focused on a number of factors associated with the occurrence of suicide, these includes- age, gender, religion, cause of death, modes of death. A total of 95 cases of suicide were studied in Sir Salimullah Medical College morgue house in the year 2008. The victims were composed of 33 males (34%) & 62 females (66%) and the age group of 21-30 years was the most common, which indicates occurrence of suicide is more common in young females. Of 95 cases, the most common cause of death was due to asphyxia, 88 cases (92%). Other cases include respiratory failure- 3 cases (3%), hemorrhage & shock- 4 cases (5%). In the discrimination of cause of death, we obtained information on victims & witness as well as investigating the scene & post mortem examination of the victim. DOI: 10.3329/bmj.v37i2.3593 Bangladesh Medical Journal 37(2) 2008 50-51